PEMANFAATAN PENGETAHUAN PADA PROGRAM SIGAP SEJAHTERA DI KABUPATEN BERAU - Mariani Bakran Rais; Laksmi Laksmi (Harmoni: Jurnal Pengabdian Kepada Masyarakat, 2021)
Utilization of knowledge  is one of the stages in knowledge management and is one of the determinants of the successful implementation of Knowledge Management. Knowledge management in general serves to facilitate the process of knowledge transfer in society. The Sejahtera Sejahtera Program is a flagship program in Berau Regency, created for the process of accelerating village development in Berau Regency towards a prosperous society. This study uses a descriptive qualitative research approach, because the researcher wants to know in depth a phenomenon that occurs through the methods of observation, interviews and document analysis. The data obtained were analyzed by qualitative data analysis used by Strauss & Corbin (2003). The results showed that the Sigap Sejahtera Fighters acted as agents of change in the utilization of knowledge in the SIGAP Sejahtera Program which were analyzed through 4 dimensions. The conclusion of the study is that the use of knowledge by the community ultimately brings changes to the social system as a consequence of the delivery of ideas that are communicated continuously.